The struggle of world powers and the future of democracy - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2022)
The problem of the future of democracy is of serious concern for the academic community of the Western countries, where democracy has been a stable form of political power. Today it is possible to discern two schools of the study of democracy – European, which is represented mostly by the researches from Germany and France, and the American one. European scholars construct a unified system of the global democratic governance, when democratic countries develop an autonomous system from bottom to top, which produces a unitary, universal model on the basis of the egalitarian cooperation. American researchers in fact envision a similar model of the global democratic governance while suggesting that it is constructed on the basis of the American model of democracy.